Accounting policies in the function of quality assessment of financial statements - Jelena Raičević (Economic Themes, 2021)
Financial statements represent an instrument by which relevant information about a company is passed on to its users. Based on the information presented in the financial statements, i.e. information on the financial position and performance of the company, and generated cash flows and capital, users make business decisions. Specific accounting policies serve as the basis for the preparation of quality financial statements. Management is responsible for the preparation and presentation of financial statements and selects accounting policies. Although simple, the issue of choosing the accounting policies can be extremely delicate and complex. Besides management, there are other stakeholders who may be affected by this issue. As a consequence, there are complex relationships that affect the choice of accounting policies, and thus the quality of financial statements.
Keywords: M41; 330; Financial statements; quality of financial statements; accounting policies